EFFECT OF GINGER EXTRACT (ZINGIBER OFCINALE ROSC.) ON CANDIDA ALBICANS ON HEAT CURED ACRYLIC RESIN PLATE - Gina Nada Maulidya; Teguh Tri Widodo; Tahta Danifatis Sunnah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Denture bases that are often used in dentistry are heat cured polymethyl methacrylate acrylic resin or heat polymerized acrylic resin. Acrylic resin has a weakness, namely the surface of the acrylic resin that can trigger the growth of bacteria and Candida albicans. Candida albicans has an important role in the occurrence of denture stomatitis. Epidemiological studies show the prevalence of denture stomatitis is quite high, ranging from 30%-50% in denture users. Innovation is needed to inhibit the growth of Candida albicans on acrylic resin, one of which is the use of ginger extract. Ginger can be antifungal because of the content of phenols and essential oils.To determine the effect of ginger extract (Zingiber ofcinale Rosc.) on Candida albicans on heat cured acrylic resin. Methods: This research design was a post test only control group design with a total sample of 24 samples. There was 3 treatment groups and 1 control group. Statistical test used One-way ANOVA Welch with post hoc Games-Howell test. Results: The results showed that there was a significant effect of 25% and 50% ginger extract on Candida albicans on heat cured acrylic resin. The Shapiro-Wilk test got normal results and the homogeneity test got inhomogeneous results. The analytic test conducted used One-way ANOVA Welch with post hoc Games-Howell and the result showed a significant differences in the 4 test groupsConclusion: There was a significant effect of 25% and 50% ginger extract in inhibiting Candida albicans on heat cured acrylic resin with an average fungal count of 2 and 1.